Interactions of maize bushy stunt phytoplasma with the leafhopper vector, Dalbulus maidis (Delong and Wolcott) (Hemiptera: Cicadellidae) and associated microbiota - Gonzalez, Javier Garcia (2016)
Phytoplasmas are bacteria with a persistent propagative transmission by insect vectors that generates direct and indirect interactions among them. In order to understand these interactions for maize bushy stunt phytoplasma (MBSP) and the leafhopper vector Dalbulus maidis (Hemiptera: Cicadellidae), two research lines were addressed. The first one aimed to determine the indirect effects of maize infection by MBSP on some biological and behavioral parameters of the vector, whereas a second line investigated direct interactions of the phytoplasma with D. maidis during its movement through the vector body following acquisition from plants, and associated microbiota. Indirect effects were investigated in choice experiments in which alighting and oviposition preferences by D. maidis were compared on healthy vs. MBSP-infected plants with variable incubation time (diseased plants with early and advanced symptoms, or still asymptomatic). Likewise, indirect effect of MBSP on the D. maidis biology was determined in two life table experiments in which the vector was reared on healthy vs. MBSP-infected plants expressing advanced disease symptoms or still asymptomatic. Choice experiments showed that alighting and oviposition preferences of D. maidis on MBSP-infected plants compared to healthy plants depend on the pathogen incubation period in the plant. The leafhopper preferred MBSP-infected plants over healthy ones during the asymptomatic phase of the disease, but rejected infected plants with advanced symptoms. The vector was able to acquire MBSP from asymptomatic infected plants shortly (3 days) after inoculation, but transmission efficiency increased when acquisition occurred at later stages of the pathogen incubation period (≥14 days) in the source plants and the test plants showed disease symptoms faster. These results suggest that MBSP modulates D. maidis preference for asymptomatic infected plants in the early stages of the crop, allowing rapid spread of this pathogen. Maize infection by the phytoplasma had a neutral effect on most life table parameters of D. maidis; a lower net reproductivity rate (Ro) was observed in the cohort reared on MBSP-infected plants with advanced symptoms, which was compensated to some extent by a higher sexual ratio. MBSP acquisition by all vector nymphal stadia was confirmed by PCR, and the pathogen as detected in both male and female reproductive organs. Concerning direct MBSP-vector interactions, transmission electron microscopy analyses showed phytoplasma-like cells in the midgut lumen, microvilli and epithelial cells, suggesting that MBSP enters the epithelium midgut through the microvilli wall. Within the epithelial cells, mitochondria and bacteria-like cells (possibly endosymbionts) were observed together with masses of phythoplasma-like cells. In the hemocoel, phytoplasma-like cells grouped into a matrix were also observed in association with bacteria-like cells similar to those observed in the midgut epithelium. Similar associations were found in the salivary gland. Interestingly, in-situ hybridization (FISH) technique revealed a variation in diversity and abundance of the microbiota in intestine and salivary glands of D. maidis adults over time after MBSP acquisition from plants. Sulcia sp., Cardinium sp. and eubacteria increased their abundance over time, whereas Rickettsia sp. decreased. The frequent association of the vector microbiota with the phytoplasma in some tissues of D. maidis suggests that endosymbiotic bacteria may play some role in MBSP-vector interactions.